Karakteristik dan Peluang Kecelakaan pada Mobil Pribadi di Wilayah Perkotaan - Lasmini Ambarwati; Harnen Sulistio; Gama Hendika Negara; Zanuar Hariadi (Rekayasa Sipil, 2010)
Growth of the number of private car in Indonesia is followed by increasing car accident. Because of thatreason, it is important to know the driver’s factors which have an effect on probability of accident in theurban area. Analysis method is logistic regression, binomial logic model with data obtained from distributionof questionnaire. From the analysis, the factors which have influence to the probability of accident in theMalang city are gender and trip purpose. Otherwise, for Batu city, gender, riding attitude, income, and traveldistance influence the probability of car accident. From driver characteristics which most drivers haveeducation background with graduated from senior high school and age below than 23 years, the probabilityof accident is 0.787.